EMERGING BOND MARKET IN THAILAND PROBLEMS AND PROSPECTS - Jyoti P. Gupta ,; I. M. Pandey ,; Titapong Techa-umponkul , (Asian Academy of Management Journal, 1996)
The Thai economic system has changed tremendously during the last 5-6 years because of its rapid growth. It is imperative for Thailand to adjust herself in order to withstand greater challenges that will be forthcoming as a result of deregulation of financial markets worldwide. With fast modernization of information and communication technology, international money and capital markets have become integrated as a financial system worldwide, and they strive to achieve efficient use of resources.